2020
DOI: 10.1155/2020/3635157
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Striga gesnerioides (Willd.) Resistance and Genetic Characterization of Forty-Six Cowpea (Vigna unguiculata (L.) Walp.) Genotypes in Ghana

Abstract: The parasitic weed, Striga gesnerioides, imposes physiological stress on cowpea (Vigna unguiculata (L.) Walp.) resulting in significant yield loss in the regions of northern Ghana. This warranted identification of resistant cowpeas for sustainable production. The current work aim was to identify Striga-resistant cowpea genotypes and assess their genetic relatedness. Forty-six (46) cowpea genotypes were screened in pots for their reaction to Striga samples obtained from the upper east, upper west, and northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The wild/weedy accessions showed more diversity than the cultivated with genetic diversity of 0.480 and 0.389, respectively. Haruna et al (2020) characterized forty-six cowpea genotypes in Ghana for resistance to Striga gesnerioides using SSR primers. The findings showed that genetic diversity ranged from 0.04 to 0.49 with an average of 0.29; and average allele frequency of 0.78 genetic diversity and the polymorphism information content (PIC) varied from 0.08 to 1.00 with an average of 0.55.…”
Section: Molecular Markers In Genetic Diversity Studiesmentioning
confidence: 99%
“…The wild/weedy accessions showed more diversity than the cultivated with genetic diversity of 0.480 and 0.389, respectively. Haruna et al (2020) characterized forty-six cowpea genotypes in Ghana for resistance to Striga gesnerioides using SSR primers. The findings showed that genetic diversity ranged from 0.04 to 0.49 with an average of 0.29; and average allele frequency of 0.78 genetic diversity and the polymorphism information content (PIC) varied from 0.08 to 1.00 with an average of 0.55.…”
Section: Molecular Markers In Genetic Diversity Studiesmentioning
confidence: 99%